THE INFLUENCE OF MOTIVATION, PERCEIVED VALUE, REFERENCE GROUP AND BRAND IMAGE ON THE PARENTS’ DECISIONS IN SELECTING YAYASAN PUPUK KALTIM SENIOR HIGH SCHOOL BONTANG - Eka Fikri Masyhuri; Dimas Hendrawan (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to explore the influence of motivation, perceived value, reference group and brand image at non-profit organization, a senior high school in Bontang city. The school‟s name is Yayasan Pupuk Kaltim Senor High School (YPK SHS). There is a changing on system  happen on the school that makes increasing on educational cost in every year. However, inreasing the new students soaring in last 2 years. As parent, school is important place to creates personalityon their kid. Quality and performance of the school are the criteria of parents for their kid. Quality and performance also have strong relation with those variable. Quantitative research method has used to explore its.The data analysis on this study uses multiple linear regression methods with 100 parents of YPK SHS‟ student as respondent. The sampling technique uses simple random sampling from purposive sampling. Validity and reliability test is used in this study with classical assumption test which is normality test, heteroscedacity test, and multicollinearity test.The result of this study shows that motivation (X1), Perceived Value (X2), Reference Group (X3), Brand Image (X4) have simultan and significant influences on parents‟ decisions in selecting YPK SHS partially. Motivation became the dominant variable in this study.Keywords: Motivation, Perceived Value, Reference Group, Brand Image, Non-profit organization, School, Decision